Association between midday napping and long-term trajectories of cognitive function among middle-aged and older Chinese adults - Jinghong Huang; Dongrui Peng; Yutong Zhang; Yanan Zhang; Xiaohui Wang (PLoS ONE, 2025)
Background The prevalence of dementia has become an increasingly important public health priority. This study investigated the association between midday napping and long-term trajectories of cognitive function in middle-aged and older Chinese adults. Methods Among 4648 participants aged 45+ years extracted from the China Health and Retirement Longitudinal Study (CHARLS). The components of the Telephone Interview of Cognitive Status battery (TICS-10) was used to assess cognitive function. Group-based trajectory modelling (GBTM) was used to identify long-term trajectories of cognitive function. Multinomial logistic regression model was used to estimate risk ratios (RRs) and 95% confidence intervals (CIs). Results Three distinct long-term trajectories of cognitive function reflected patterns of rapid decline, slow decline, and stable. The RR (95% CI) for rapid decline was 1.45 (1.05–2.01) for 0 minutes, 1.49 (1.05–2.12) for 31–90 minutes, and 2.19 (1.41–3.42) for >90 minutes compared with midday napping 1–30 minutes. The RR (95% CI) for slow decline was 1.22 (1.02–1.47) for 0 minutes, 1.27 (1.04–1.55) for 31–90 minutes, and 1.80 (1.38–2.35) for >90 minutes compared with midday napping 1–30 minutes. In addition, the increased risk of cognitive decline that transferred from >90 to 31–90 minutes, switched from 31–90 to >90 minutes, and persisted in >90 minutes compared with midday napping 1–30 minutes, especially rapid decline. Conclusions There was a longitudinal association between no and long (>30 minutes) midday napping and long-term trajectories of cognitive decline, especially rapid decline. The study is a 4-year observational in nature and provides limited evidence for establishing causal relationships.